Phytochemical composition and biological activities of extracts from Astragalus membranaceus arieal parts - Mohamed El Amine Smaali; Fadila Khaldi; Maya Bouafia; Fatima Kerroum; Mohamed Abidi; Mohamed Lahmadi; Nassim Madi; Barbara Sawicka; Sheikh F. Ahmad; Sabry M. Attia; Wafa Zahnit; Mohammed Messaoudi (International Journal of Food Properties)
The application of biomolecules extracted from plants in food and pharmaceutical industry is of great interest. In the light of that fact, our interest has been aroused to study the efficiency of chlorophormic and ethyl acetat solvents for the extraction of the main molecules from Astragalus membranaceus aerial parts (AMA) in order to evaluate the antioxidant, inhibition of α-amylase and Angiotensin-Converting Enzyme (ACE), antibacterial, cytotoxic activies and in vitro DNA-protective capacity of these extracts. Gas chromatography-mass spectrometry (GC-MS) analysis showed the presence of methyl petroselinate acid as the main compound (45, 87%) in the ethyl acetate extract (EA-AMA) and the main compound in the chloroform extract (C-AMA) was linolenic acid (16.95%). The ethyl acetate extract exhibited strong antioxidant activity with interesting IC50 values not exceeding 40 μg/mL in almost all activities. The highest in vitro activity against α-amylase and ACE activity was obtained from chloroform extract with an IC50 of 20.36 and 20.77 µg/ml, respectively. The resazurin microtiter assay was carried out to analyze the extract potential against multi drug resistant strains of clinical bacteria origin of which the extracts had powerful antibacterial activity with minimum inhibitory concentration against Pseudomonas aeruginosa (0.039 ± 0 mg/ml) and Escherichia coli (0.039 ± 0 mg/ml). The extracts had a strong protective effect of Fenton-induced DNA damage. The XTT test revealed that the extracts had weaker cytotoxicity profile against EMT6 cell line. These findings suggest that this plant has a wide range of potential applications as a food supplement, a preventative and medicinal agent.